Penggunaan Media Wordwall untuk Meningkatkan Hasil Belajar Siswa Kelas X SMAN 1 Pademawu - Damayanti, Riska; Wachidah, Liana Rochmatul (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
Indonesian language learning that keeps up with the times can be realized through the use of internet-based technology media. Technology-based media will maximize the targets of Indonesian language learning. Many learning platforms can be applied in learning Indonesian, some are paid and some are free. One of the applications that can be used in learning Indonesian is Wordwall. In this study, Wordwall is applied in Indonesian language learning on the material of observation report texts in high school. The subjects of this research are 10th-grade students at SMAN 1 Pademawu. This research is in the form of classroom action research. The research results show that the students' success rate in mastering observation report texts at the pre-cycle stage was 42.8%, at the cycle I stage was 64%, and at the cycle II stage was 85.7%. This indicates an increase in the graph of students' mastery of observation report text material after using Wordwall as a learning medium. There are still several obstacles in the use of that media, namely network issues and students' concentration not yet improving to the maximum.